1999
DOI: 10.2307/3285637
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Hemoglobin-like Protein from Adult Haemonchus contortus

Abstract: A hemoglobin-like protein was purified from supernatants of adult Haemonchus contortus extracts by high-pressure liquid chromatography. The purified protein had an M(r) of 33 kDa as determined by size-exclusion chromatography under non-denaturing conditions and an M(r) of 19 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, suggesting the hemoglobin may exist as a dimer. The sequences of 3 peptides resulting from proteolytic digest of the purified protein were determined and demonstrated greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The present results are in accordance with Fetterer et al (1999); Gomez-Munoz et al (1996); Selvarayar Arunkumar (2012), who purified proteins from H. contortus and their molecular weights were almost similar to what are reported in the present study. Here it is important to mention that the results so obtained in the present study may vary which may be due to difference in preparing the solutions, chemical reagents of different quality and quantity or application procedures (Norouzi et al 2007).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The present results are in accordance with Fetterer et al (1999); Gomez-Munoz et al (1996); Selvarayar Arunkumar (2012), who purified proteins from H. contortus and their molecular weights were almost similar to what are reported in the present study. Here it is important to mention that the results so obtained in the present study may vary which may be due to difference in preparing the solutions, chemical reagents of different quality and quantity or application procedures (Norouzi et al 2007).…”
Section: Resultssupporting
confidence: 93%
“…3). Ashman et al (1995) purified a 70-90 kDa larval protein from H. contortus ;Fetterer et al (1999) purified protein from adult H. contortus and its molecular weight was determined as 33 kDa by SDS-PAGE; Gomez-Munoz et al (1996) identified and purified a 26 kDa protein partially from H. contortus by SDS-PAGE; Crab et al (2002) partially purified 23.8 kDa protein from this parasite; Rathore et al (2006) identified 66 kDa excretory secretory antigen from H. contortus; Prasad et al (2007) recognized 60 and 120 kDa polypeptides from H. contortus by immunoaffinity chromatography and SDS-PAGE; Selvarayar Arunkumar (2012) on characterization of purified E/S antigen of H. contortus by SDS-PAGE revealed a single band at 66 kDa; Clarke and Slocombe (1984) observed a single band corresponding to a molecular weight of 172,000 Da from exsheathing fluid and somatic extracts of H. contortus; Siamba et al (2012) observed 13 major peptide bands in SDS PAGE of infective L 3 larvae of H. contortus and observed a specific 46 kDa protein in unstressed parasites and 32 kDa protein in stressed ones.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support previous evidence showing that, for example, cysteine peptidases play a crucial role in the catabolism of globin by the cleavage of hemoglobin in blood-feeding nematodes [22-25]. Concomitantly, in the blood-feeding stages, we observed upregulated transcription of genes encoding succinate dehydrogenase subunit B and glutamate dehydrogenase genes via the respiratory electron transport chain [26] (proposed to maintain the redox balance in response to the accumulation of the end products from anaerobic metabolism [27]), and hemoglobin-like proteins [28] (probably involved in oxygen uptake, osmotic regulation, iron storage and/or oxygen-detoxification [29]). We also found increased transcription of genes encoding enzymes, including glutathione S-transferase, cytoplasmic Cu/Zn superoxide dismutase, catalase, glutathione peroxidase and/or peroxiredoxin, which are likely to have roles in heme transport or detoxification of reactive oxygen species from endogenous metabolic activities from the host during H. contortus infection; this is supported by findings from previous investigations [30-32] and recognized as characteristic of tissue-dwelling or blood-dwelling parasites [32].…”
Section: Resultsmentioning
confidence: 99%
“…Aliquots containing the purified MOP were pooled and stored at Ϫ80 C. A 50-L fraction of purified MOP was submitted to matrix-assisted laser deabsorption-time of flight (MALDI-TOF) mass spectroscopic analysis to confirm molecular mass (Rhoads et al, 2000). An aliquot of the purified MOP was run on a polyacrylamide gel, and the 2 bands corresponding to MOP were excised from the gel, and each was subjected to trypsin fractionation, MALDI-TOF analysis of tryptic digest, and internal sequence analysis by automated Edman degradation (Fetterer et al, 1999;Rhoads et al, 2000).…”
Section: Protein Purificationmentioning
confidence: 99%